Individuals with a previous symptomatic COVID-19 infection have altered heart rate and blood pressure variability during acute exercise - Chan, Jillian; Senior, Hailey; Homitz, Jessica; Cashin, Niamh; Guers, John J. (Frontiers in Physiology, 2023)
Introduction: As the number of COVID-19 cases begin to diminish it is important to turn our attention to any long-term issues that may be associated with a prior infection. Cardiovascular defects have been noted following prior SARS-CoV-2 infections. However, less is known about how a previous infection alters the cardiovascular response to exercise. Further, differences may exist during exercise between previously SARS-CoV-2 positive individuals who had symptoms (symptomatic) relative to those who did not have symptoms (asymptomatic). We hypothesized that previously symptomatic (S) COVID-19 recoveries have an altered cardiovascular response to acute exercise relative to both control (CON; never infected), and previously COVID-19 positive asymptomatic (AS) individuals. Methods: Twenty-seven subjects (CON = 9; AS = 9; S = 9) underwent 30 min of submaximal treadmill exercise. During exercise, blood pressure was recorded on the brachial artery every 5 min and 3-lead electrocardiography was measured continuously. Indirect indicators of autonomic nervous system health: heart rate variability and blood pressure variability were measured during each session. Baseline mean arterial pressure (MAP) was taken prior to exercise in seated, standing and supine positions. Results: Blood pressure was similar (p > 0.05) amongst all three groups. There were no differences between average heart rate (HR; CON = 104 ± 4 BPM vs AS = 118 ± 6 BPM vs. S = 112 ± 3 BPM), mean arterial pressure (MAP; CON = 108 ± 4 mmHg vs. AS = 105 ± 13 mmHg vs. S = 108 ± 7 mmHg) or oxygen consumption (VO2) between groups during a bout of exercise. However, the standard deviation of the inter beat intervals of normal sinus beats, a measure of heart rate variability (HRV) (CON = 138 ± 2.8 m vs. AS = 156 ± 6 m vs. S = 77.7 ± 11 m; p < 0.05) and blood pressure variability (BPV; CON = 5.18 ± 1.1 vs. AS = 12.1 ± 0.88 mmHg vs. S = 10.2 ± 10.7 mmHg; p < 0.05) were different in our S group. Further, when HRV was assessed in the frequency domain the very low frequency was different during exercise in the S group relative to the other groups. Discussion: Collectively, these data suggest that a previous symptomatic SARS-CoV-2 infection may alter heart rate and blood pressure regulation during exercise.